High Nitrogen Supply Induces Physiological Responsiveness to Long Photoperiod in Barley - Zeng, Jian; Sheng, Huajin; Liu, Yang; Wang, Yao; Wang, Yi; Kang, Houyang; Fan, Xing; Sha, Lina; Yuan, Shu; Zhou, Yonghong (Frontiers in Plant Science, 2017)
Photoperiod and the nutrient nitrogen influence growth, development and productivity in crop plants. In this study, physiological, biochemical and morpho-anatomical traits of two barley cultivars (NA5 and NA9) with contrasting photoperiod length were examined under the combined treatment of photoperiod regime and nitrogen supply. Under long photoperiod, high nitrogen decreased the net photosynthesis, chlorophyll a, chlorophyll a/b, antioxidant enzyme activities of ascorbate peroxidase (APX), catalase (CAT) and superoxide dismutase (SOD), the concentration of ascorbate (AsA), glutathione (GSH), soluble protein and soluble sugar and destroyed the mesophyll cell integrity, while increased O2•-, malonaldehyde (MDA) and proline (Pro) in both NA5 and NA9. Under short photoperiod, high nitrogen increased the net photosynthesis, chlorophyll a, chlorophyll a/b, activities of APX, CAT and SOD, antioxidants, soluble protein and soluble sugar in NA9 but decreased these above parameters in NA5. These results indicated that photosynthetic capacity and reactive oxygen species balance was strongly affected by the nitrogen supply level in response to short and long photoperiod. High nitrogen enhanced sensitivity to photoperiod change in long day barley by inhibiting photosynthesis and decreasing antioxidant defense ability and mitigated undesirable effects of shortening photoperiod in short day barley. Therefore, the data from this study indicated that nitrogen status affect adaptation to photoperiod change due to redox homeostasis and maintaining photosynthetic capacity.